2022
DOI: 10.2147/clep.s366874
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ICD-9-CM and ICD-10-CM Diagnostic Codes for Identifying Patients with Out-of-Hospital Cardiac Arrest in a National Health Insurance Claims Database

Abstract: Purpose Taiwan’s national health insurance (NHI) database is a valuable resource for large-scale epidemiological and long-term survival research for out-of-hospital cardiac arrest (OHCA). We developed and validated case definition algorithms for OHCA based on the International Classification of Diseases (ICD) diagnostic codes and billing codes for NHI reimbursement. Patients and Methods Claims data and medical records of all emergency department visits from 2010 to 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In 11 reports, investigators evaluated diagnosis codes in the electronic medical record system of convenience sample of selected hospital(s), using manual review of medical records, data from an existing stroke registry, or the Taiwan Death Registry as gold standard 33–43 (Table 4). The validation results were major findings in all 11 articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 11 reports, investigators evaluated diagnosis codes in the electronic medical record system of convenience sample of selected hospital(s), using manual review of medical records, data from an existing stroke registry, or the Taiwan Death Registry as gold standard 33–43 (Table 4). The validation results were major findings in all 11 articles.…”
Section: Resultsmentioning
confidence: 99%
“…30 In the other report the survey subjects served as a validation subgroup to evaluate the diagnosis codes for tuberculosis, with the Tuberculosis Registry of Taiwan Centers for Disease Control 31 as gold standard, and the validation result was not a major focus of the report. 32 In 11 reports, investigators evaluated diagnosis codes in the electronic medical record system of convenience sample of selected hospital(s), using manual review of medical records, data from an existing stroke registry, or the Taiwan Death Registry as gold standard [33][34][35][36][37][38][39][40][41][42][43] (Table 4). The validation results were major findings in all 11 articles.…”
Section: Usingmentioning
confidence: 99%
“…Our previous study indicated that this transition had an impact on the validity of identifying out-of-hospital cardiac arrest cases using ICD-10-CM-based algorithms, with an observable decrease in validity in the first year after the transition. 24 This might be due to unfamiliarity with the new coding system and potential coding errors. To examine whether a similar issue existed in the development of our algorithms, we performed a subgroup analysis to assess the accuracy of the algorithm in different years.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other cardiovascular diseases, such as acute coronary syndrome or cardiac arrest, [36][37][38][39][40] the PPV of ICD-10-CM codes for myocarditis is not well understood. To the best of our knowledge, there has been only one validation study, conducted in the Danish National Patient Registry, which reported the PPV of myocarditis (I40, I41, I090, I514) to be 80% as primary diagnosis, and 36% as secondary diagnosis.…”
mentioning
confidence: 99%